358 The relationship between serum biomarkers of traumatic brain injury (TBI) and magnetic resonance imaging (MRI) in patients discharged from the emergency department (ED) with a normal acute CT. Issue 12 (23rd November 2020) - Whitehouse, Daniel; Richter, Sophie; Czeiter, Endre; Winzeck, Stefan; Kornaropoulos, Evgenios N; Das, Tilak; Vyvere, Thijs Vande; Verheyden, Jan; Williams, Guy B; Correia, Marta M; Wang, Kevin; Menon, David K; et al.
Abstract : Aims/Objectives/Background: CT remains the neuroimaging of choice in patients with TBI, however the relative lack of sensitivity as compared to MRI for certain traumatic lesion types, including diffuse axonal injury (DAI), could lead to missing important intracranial findings. 1 Serum biomarkers may allow screening of ED patients, highlighting those who will benefit from MRI and offer a pathway for further imaging in mild TBI patients. Methods/Design: Patients discharged from ED with a panel of 6 biomarkers (GFAP, NFL, NSE, S100B, t-tau and UCH-L1), acute CT < 24 hrs of injury and acute MRI, were extracted from the CENTER-TBI core dataset. 2 Mann Whitney U test to compare median biomarker levels in relation to +ve or –ve MRI. Unadjusted Area Under ROC (AUC) calculated for detection of MRI abnormality. Results/Conclusions: 80 patients met inclusion criteria, 45 (56%) male, median age 36.5 yr [IQR 24.5–51.3], median GCS 15 [IQR 15–15]. 17/80 (21.25%) had MRI abnormalities. 1 intraventricular haemorrhage, 2 traumatic subarachnoid haemorrhages, 3 intraparenchymal haemorrhages and 13 DAI. Of the biomarkers (median): GFAP (0.28 vs 1.88 ng/ml, p = 0.002), NSE (13.08 vs 15.19 ng/ml, p= 0.013), S100B (0.06 vs 0.12 µg/L, p=0.002), t-tau (0.82 vs 1.58 pg/ml, p=0.002), UCH-L1 (22.33 vs 57.68 pg/ml p<0.001) were significantly raised in patients with MRI abnormality. Serum NFL concentration was not significant (5.80 vs 8.18 pg/ml, p=0.096). AUC [95% CI] for detection of MRI abnormality: GFAP (0.75 [0.61–0.89]), NFL (0.63 [0.48–0.79]), NSE (0.70 [0.55–0.85]), S100B (0.75 [0.61–0.90]), tau (0.75 [0.61–0.89]), UCH-L1 (0.82 [0.69–0.95]) The results demonstrate potential utility in several acute serum biomarkers for screening of patients with a negative CT. Fair discrimination for detection of MRI pathology in this cohort was demonstrated by GFAP, NSE, S100B, total tau and UCH-L1. Further prospective analysis is required to assess the utility for biomarkers to determine MRI requirement in an ED population. References: Metting Z, Rödiger LA, De Keyser J, et al . Structural and functional neuroimaging in mild-to-moderate head injury. Lancet Neurol 2007;6 :699–710. doi:10.1016/S1474-4422(07)70191-6 Maas AIR, Menon DK, Steyerberg EW, et al . Collaborative European neurotrauma effectiveness research in traumatic brain injury (CENTER-TBI): A prospective longitudinal observational study. Neurosurgery 2015;76 :67–80. doi:10.1227/NEU.0000000000000575